Application of Rebuke Techniques and Spiritual Remembrance Therapy for Hallucination Patients in the Purbaratu Community Health Center,Tasikmalaya City - Asep Riyana (Politeknik Kesehatan Kementerian Kesehatan Banten, 2024)
Hallucinations are one of the symptoms of mental disorders in individuals characterized by sensory alterations of perception , perceiving false sensations in the form of sounds, visions, tastings, touching or discolorations that actually feel a stimulus that no client who experiences hallucinations can lose control of himself so as to harm himself, others and the environment. How to control hallucinations, one of which is to rebuke hallucinations by rejecting the hallucinations that appear can control hallucinations. Zikir is defined as all kinds of forms of remembering Allah, mentioning the name of Allah, either by reading tahlil, prayer beads, tahmid, taqdis, takbir, tasmiyah, hasbalah, asmaul husna, or reading prayers that are mat'sur from the Prophet Muhammad SAW. knowing the description of the application of rebuking techniques and zikir spiritual therapy, knowing the ability to control hallucinations after rebuking techniques and zikir spiritual therapy are carried out. The design in this study is qualitative with a case study approach to explore problems in hallucinatory patients using rebuking techniques and spiritual therapy. Data collection with assessment and instruments of signs and symptoms as well as instruments of the ability to control hallucinations. The results of the second study of patients after the act of rebuking and spiritual therapy suggested a decrease in the signs and symptoms of hallucinations as well as the ability to control the patient's hallucinations. In patient 1 there was a decrease in signs and symptoms by 7 signs and symptoms, in patient 2 as many as 4 signs and symptoms. The conclusion after the implementation of the technique of rebuking and spiritual therapy of thought the researcher was able to describe the application, signs and symptoms, the ability to constrict hallucinations. Suggestions for other studies to study in more depth and in conducting research can use a longer time so that the data obtained are more accurate and more convincing that the application of rebuking and spiritual therapy can be useful when hallucinations appear.